KAJIAN BHISAMA KAWITAN CATUR RSI UNTUK GENERASI MUDA PASEK - Made Adi Nugraha Tristaningrat (Purwadita : Jurnal Agama dan Budaya, 2019)
Bhisama is a set of provisions authority and wates-wates. Further it says Bhisama canbe interpreted as a message, it can be seen in Parva Parva-as in the Shalya Parva. Ida PedandaPemaron States that Bhisama is a word that contains a magical and sacred meaning, in oldJavanese called tuah. The word Bhisama can also be compared with the word pemastu that is aword that is very Holy and sacred. Bhisama is also similar to the sense of the word tantu (e.g.Tantu Performances). He further stated that the Bhisama was a dagger, pemastu and can organizeyour expected tantu, directing behavior of the Hindus. Bhisama is a command ¬-command(either in the form of pewarah-warah, and advice-advice) or prohibitions (piteket-piteket) whichis expected to be organizing, directing behavior of Hindus. For those who violate pewarah ¬warah, advice-advice or piteket-piteket would be fatal for the violators (will be subject to severesanctions and dangerous) form of the curses that are very incriminating and dangerous. Bhisamais issued by a Tribunal or pandita pandita (Paruman Pandita), people who are downright sacredgood views of knowledge, attitude and proved it everyday (running religious teachings especiallyTri Kaya Parisudha).